2019
DOI: 10.1021/acschemneuro.8b00440
|View full text |Cite
|
Sign up to set email alerts
|

d-Enantiomeric RTHLVFFARK-NH2: A Potent Multifunctional Decapeptide Inhibiting Cu2+-Mediated Amyloid β-Protein Aggregation and Remodeling Cu2+-Mediated Amyloid β Aggregates

Abstract: Aggregation of amyloid β-protein (Aβ) into β-sheet-rich plaques is a general feature of Alzheimer’s disease (AD). Homeostasis dysregulation of Cu2+ mediates Aβ to form high cytotoxic aggregates, which causes cell damage by generation of reactive oxygen species (ROS). To improve the inhibitory potency and explore the multifaceted functions of our previously designed decapeptide, RTHLV­FFARK-NH2 (RK10), we have herein reformulated the decapeptide into its d-enantiomer, rk10, and the effects of chirality on Aβ ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
5
21
0
Order By: Relevance
“…1−4 The attenuation of Aβ accumulation toward alleviating amyloid-associated neurotoxicity has been considered as a promising therapeutic strategy for AD treatment. Many efforts have been done to develop different agents for inhibiting Aβ fibrillization, such as small organic molecules, 5,6 peptides, 7,8 proteins, 9 and nanoparticles. 10,11 Moreover, the remodeling or disassembly of performed Aβ aggregates has recently attracted wide attention.…”
Section: Introductionmentioning
confidence: 99%
“…1−4 The attenuation of Aβ accumulation toward alleviating amyloid-associated neurotoxicity has been considered as a promising therapeutic strategy for AD treatment. Many efforts have been done to develop different agents for inhibiting Aβ fibrillization, such as small organic molecules, 5,6 peptides, 7,8 proteins, 9 and nanoparticles. 10,11 Moreover, the remodeling or disassembly of performed Aβ aggregates has recently attracted wide attention.…”
Section: Introductionmentioning
confidence: 99%
“…Reciprocally, Aβ has several pathways to induce cells to overexpress ROS and then increase oxidative stress. For instance, metal ion-chelate Aβ can restore the O 2 through a three-step cycle where O 2 is gradually reduced to superoxide and oxygen peroxide, eventually forming OH radicals and generating ROS as byproducts [34][35][36]. Moreover, Aβ can also directly stimulate oxidative stress through endoplasmic stress, lipid peroxidation, and mitochondria dysfunction [37][38][39].…”
Section: Oxidative Stress and Neurodegenerative Diseasesmentioning
confidence: 99%
“…Prompted by the need to pursue effective treatment of AD, many inhibitors against Aβ aggregation and cytotoxicity were explored, including small molecules, peptides [ 17 , 18 , 19 ], proteins [ 20 , 21 , 22 ] and antibodies [ 23 ]. For example, we demonstrated that 5,10,15,20-tetrakis(N-methyl-4-pyridyl)-porphyrin (TMPyP), a water-soluble porphyrin, can inhibit Aβ aggregation, disintegrate the preformed Aβ aggregates and alleviate Aβ-induced cytotoxicity [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22] peptide[84]. Moreover,Kim et al reported that a C 60 derivate(1,2-dimethoxymethanofullerene) could bind to the central motif, namely, Aβ 16-20 (KLVFF), based on the strong hydrophobic interaction and inhibit the aggregation of Aβ peptides at the early stage[85].…”
mentioning
confidence: 99%